Pengaruh Kemampuan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Dinas Perpustakaan Dan Kearsipan Kota Pekanbaru - Mei S, All Ouxtrisa Chandra; Praweswari, Utari; Turrahmah, Masyithoh; Liza, Delfina Mei (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
This study aims to see the effect of employee performance and organizational culture on employee performance at the Pekanbaru City Library and Archives Service. Sources of data obtained directly from the distribution of the questionnaire. The population in this study were employees of the Pekanbaru City Library and Archives Service with a total sample of 40 people who were taken using probability sampling technique. The data analysis method used analysis of validity test, reliability test, partial test, simultaneous test, and coefficient of determination test. The results of this study indicate that there is a positive and significant influence between work ability and organizational culture simultaneously on the performance of the Pekanbaru City Library and Archives Office employees